Characteristics and Properties of Epoxy/Polysulfide Blend Matrix Reinforced by Short Carbon and Glass Fibers - Mahmood, Ibtihal A.; Shamukh, Mustafa Ziyara (Al-Nahrain Journal for Engineering Sciences, 2017)
In this research, binary blends have been prepared from epoxy resin (EP) and different weight percentages of polysulfide rubber (PSR) (0%, 2.5%, 5%, 7.5 and 10%), and then compression, impact, and hardness tests were evaluated. The experimental results showed that the addition of polysulfide rubber in the epoxy resin decreased the compressive strength, Young’s modulus, and hardness, while increased the impact resistance. It was found that the weight percentage 5% of polysulfide was the best percentage, which gives the best mechanical properties for the blend matrix. The advantage of this blend matrix is that, it mediates between the brittle properties of epoxy and the flexible properties of a blend matrix with the highest percentage of PSR. Short fibers (Carbon & Glass) with different volume percentage (2.5%, 5%, 7.5%, and 10%), were used to reinforce the best blend matrix obtained separately and randomly, and then the same mechanical tests conducted on these composites. The experimental results showed that the addition of fibers increased the compressive strength, Young’s modulus, impact resistance and hardness. It was also observed that the composites materials reinforced with carbon fibers have significantly higher mechanical properties values than the composites materials reinforced with glass fibers.